PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN MODEL PROBLEM POSING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI SISWA KELAS X.2 SMA NEGERI 2 KARANGANYAR TAHUN PELAJARAN 2011/2012 - Suparmi, Suparmi; Suciati, Suciati; Harlita, Harlita (Pendidikan Biologi, 2013)
ABSTRACT ? This research aims to improve  low quality of biology  in class X.2 SMA Negeri 2 Karanganyar in academic year 2011/2012. Learning considered by  teacher?s performance, utility of facilities in the classroom, classroom climate, student?s scientific attitude, and student motivation of achievement applying for approach Contextual Teaching and Learning with Problem Posing model.  This research was a classroom action research which and performed  in three  cycles. Each  cycle  consisted  of  4  phases, namely planning, action, observation, and reflection. The data  was  collected Tes and Non Tes by question, questionnaire, observation,  and manual interview. Data validation was used triangulation of methods and triangulation of observers. The obtained data were analyzed using descriptive technique.  The results of this research showed that according triangulation the average percentage for  teacher?s performance in  pre cycle (60%), cycle I (86,67%), cycle II  (96,67%) and cycle III (100%);  classroom climate  pre cycle (54,16%), cycle I (68,05%), cycle II (76,38%) and cycle III (86,80%);  student?s scientific attitude    pre cycle (50,92%), cycle I (65,27%), cycle II (74,07%) and cycle III (83,79%); and  student motivation of achievement  pre cycle (57,71%), cycle I (65,75%), cycle II (74,38%) and cycle III (85,80%);  utility of learning facilities in the classroom have been optimally. The  results  showed  that  the  average  percentage  quality of   biology  learning  aspect such as  pre cycle (55,69%),  cycle I (71,43%), cycle II (80,37%) and cycle III (89,09%) (increase 33,4% from pre cycle to cycle III).  Cycles stopped in cycle III because the research target is achieved. The conclusion of this research describes that  the implementation of approach contextual teaching and learning with problem posing model  can improve quality of  biology  learning  considered by  teacher?s performance, utility  of facilities in the classroom,  classroom  climate,  student?s scientific attitude,  and student motivation of achievement in class X.2 at SMA Negeri 2 Karanganyar in academic year 2011/2012. Keywords: Contextual teaching and learning, Problem posing, Quality of biology Learning